Sedentism, Social Change, Warfare, and the Bow in the Ancient Pueblo Southwest. Issue 3 (17th June 2013) - Reed, Paul F.; Geib, Phil R.
<x xml:space="preserve">Abstract</x> In the ancient American Southwest, use of the bow developed relatively rapidly among Pueblo people by the fifth century AD. This new technology replaced the millennia‐old atlatl and dart weaponry system. Roughly 150 years later in the AD 600s, Pueblo socioeconomic organization began to evolve rapidly, as many groups adopted a much more sedentary life. Multiple factors converged to allow this sedentary pattern to emerge, but the role of the bow in this process has not been fully explored. In this paper, we trace the development of the bow and discuss its role as sedentism emerged and social changes occurred in ancient Puebloan society from the fifth through seventh centuries AD.